REVOLUTIONIZING ELEMENTARY SCIENCE EDUCATION: IMPACT OF INTERACTIVE VISUAL MEDIA ON LEARNING THE HUMAN RESPIRATORY SYSTEM - Faniningsih Ardila Putri; Arif Rahman Hakim; Syahriani Yulianci; Arif Hidayad; Zulharman (CV. TOTUS TUUS, 2025)
The persistent difficulty students face in understanding the human respiratory system—a core yet abstract topic in science education—is rooted in the lack of contextual, visual, and interactive learning media, as highlighted by both national and international research. This study aimed to examine whether technology-based, visual respiratory system media can significantly enhance elementary students’ cognitive learning outcomes, particularly in higher-order thinking skills such as analysis and evaluation. Employing a quantitative, quasi-experimental one-group pretest-posttest design, the study involved 34 fifth-grade students at SDN Inpres Rasa 1, Kabupaten Bima, using purposive sampling. A 20-item multiple-choice test based on the revised Bloom’s taxonomy (C1–C4) was used to measure learning outcomes before and after intervention. Descriptive statistics showed a marked improvement: the mean pretest score was 62.8, rising to 73.3 in the posttest, with gains observed across all ability levels. Inferential analysis using a paired sample t-test confirmed the significance of this improvement (t = -15.2, df = 33, p < .001), demonstrating that interactive visual media have a strong positive effect on students’ conceptual understanding of the respiratory system. The results conclude that technology-based visual media not only promote retention and comprehension but also foster analytical and evaluative skills, aligning with current science education goals. This research provides empirically-tested, practical recommendations for educators and policymakers, supporting the integration of digital media in science curricula and teacher training. Future studies are recommended to expand this approach with control groups, longitudinal designs, and investigations into affective and psychomotor domains, as well as the use of emerging technologies like augmented reality and virtual reality to further enhance science learning outcomes.